Digestibility and Silage Quality of Potato Pulp Silages Prepared with Different Feedstuff - ŞENYÜZ ΗΗ; KARSLI ΜΑ (Journal of the Hellenic Veterinary Medical Society, 2022)
The objective of this study was to determine silage quality and digestibility of potato pulp ensiled with different feedstuffs (straw, alfalfa hay and wheat bran). A total of 5 different potato pulp silages (PPS) were prepared with 5% ground barley straw, ground alfalfa hay, wheat bran alone or combination of 2.5 % wheat bran+ground straw, and wheat bran+ground alfalfa hay on a fed basis.These silages were ensiled in 2-L jars. After 49d of ensiling, all silages were opened and the chemical composition, pH, organic acids, ammonia-N contents, in situ organic matter (OM) and starch degradabilities and in vitro OM digestibility (IVOMD) of the silages were determined. Then, energy values were calculated.The highest dry matter (DM) and OM concentrations were observed in PPS prepared with wheat bran alone (P<0.05). Potato pulp silage containing ground barley straw alone had the lowest crude protein (CP) concentration (P<0.05) and silage containing wheat bran alone had the lowest neutral detergent fiber (NDF) and acid detergent fiber (ADF) concentrations among PPS (P<0.05). Potato pulp with wheat bran alone had the highest lactic acid concentrations among all silages (P<0.05). Acetic acid concentrations of silages were similar (P>0.05). The in situ OM degradability and IVOMD were significantly different (P<0.05) among all silages. However, in situ starch digestibility was similar among PPS (P>0.05). It can be concluded that PPS prepared with different feedstuffs at a 5% level had good fermentation properties and high degradability values. Even a high quality PPS can be obtained with the addition of 5% ground barley straw alone.